2015
DOI: 10.1093/annonc/mdu509
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the outcome of young breast cancer patients in the UK: the POSH study

Abstract: Young obese breast cancer patients present with adverse tumour characteristics. Despite adjustment for this, obesity still independently predicts DDFI and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 24 publications
3
77
0
2
Order By: Relevance
“…Several clinical trials have demonstrated that obesity at diagnosis is associated with breast-cancer-specific survival (BCSS) and a1111111111 a1111111111 a1111111111 a1111111111 a1111111111 overall survival (OS) [1][2][3], which was additionally supported by recent meta-analyses [4]. However, other studies have found no association between BMI and the prognosis of breast cancer [5][6][7].…”
Section: Introductionmentioning
confidence: 93%
“…Several clinical trials have demonstrated that obesity at diagnosis is associated with breast-cancer-specific survival (BCSS) and a1111111111 a1111111111 a1111111111 a1111111111 a1111111111 overall survival (OS) [1][2][3], which was additionally supported by recent meta-analyses [4]. However, other studies have found no association between BMI and the prognosis of breast cancer [5][6][7].…”
Section: Introductionmentioning
confidence: 93%
“…In clinical condition, the association between obesity and HER2-overexpressing breast cancer is perplexing [148], [149], [150]. Nonetheless, Tan et al [151] recorded that the fat mass and obesity-associated (FTO) gene expression in the HER2-overexpressed subtype of breast cancer was significantly higher.…”
Section: Clinical Studies On Breast Cancer and Her2 With Reference Tomentioning
confidence: 99%
“…On the contrary, fat tissue shows increased levels of leptin, resulting in low TGF‐β and IL‐10 levels. However, obese breast cancer patients still have higher mortality, which may be a result of the association between obesity and increased tumor size, positive lymph node involvement, and triple‐negative subtype, but not the secretion of TGF‐β and IL‐10 . Other nutritional parameters were not significantly associated with levels of TGF‐β, IL‐10 and Foxp3, potentially because there is a nondirect correlation between them in terms of biological mechanism.…”
Section: Discussionmentioning
confidence: 94%